Having Medicaid insurance negatively impacts outcomes in patients with head and neck malignancies. Issue 22 (1st August 2016) - Naghavi, Arash O.; Echevarria, Michelle I.; Grass, G. Daniel; Strom, Tobin J.; Abuodeh, Yazan A.; Ahmed, Kamran A.; Kim, Youngchul; Trotti, Andy M.; Harrison, Louis B.; Yamoah, Kosj; Caudell, Jimmy J.
Abstract : BACKGROUND: Patients covered by Medicaid insurance appear to have poorer cancer outcomes. Herein, the authors sought to test whether Medicaid was associated with worse outcomes among patients with head and neck cancer (HNC). METHODS: The records of 1698 patients with squamous cell HNC without distant metastatic disease were retrospectively reviewed from an institutional database between 1998 and 2011. At the time of diagnosis, insurance status was categorized as Medicaid, Medicare/other government insurance, or private insurance. Outcomes including locoregional control (LRC) and overall survival (OS) were estimated using the Kaplan‐Meier method and Cox regression multivariate analysis (MVA). RESULTS: The median follow‐up for all patients was 35 months. Medicaid patients comprised 11% of the population; the remaining patients were privately insured (56%) or had Medicare/government insurance (34%). On MVA, Medicaid patients were younger, were current smokers, had higher tumor T and N classifications, and experienced a longer time from diagnosis to treatment initiation (all P <.005). Medicaid insurance status was associated with a deficit of 13% in LRC (69% vs 82%) and 26% in OS (46% vs 72%) at 3 years (all with P <.001). A time from diagnosis to treatment initiation of >45 days was found to be associated with worse 3‐year LRC (77% vs 83%; P  = .009) and OS (68% vs 71%; P  = .008). On MVA, Medicaid remained associated with a deficit in LRC ( P  = .002) and OS ( P <.001). CONCLUSIONS: Patients with Medicaid insurance more often present with locally advanced HNC and experience a higher rate of treatment delays compared with non‐Medicaid patients. Medicaid insurance status appears to be independently associated with deficits in LRC and OS. Improvements in the health care system, such as expediting treatment initiation, may improve the outcomes of patients with HNC. Cancer 2016;122:3529–3537 . © 2016 American Cancer Society Abstract : Medicaid insurance status appears to independently predict for a deficit in 3‐year locoregional control and overall survival in patients with head and neck cancer. Having Medicaid insurance also is associated with a longer time from diagnosis to treatment initiation, a variable that is associated with locoregional control and overall survival, and a likely contributing factor to the poor outcome noted among patients with head and neck cancer who have Medicaid insurance.